A New International Division of Labor in Europe: Outsourcing and Offshoring to Eastern Europe - Dalia Marin (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
Europe is reorganizing its international value chain. I document these changes in Europe's international organization of production with new survey data of Austrian and German firms investing in Eastern Europe. I show estimates of the share of intrafirm trade between Austria or Germany on the one hand and Eastern Europe on the other. Furthermore, I present empirical evidence of the drivers of the new division of labor in Europe. I find among other things that falling trade costs and reduced levels of corruption as well as improvements in the contracting environment in Eastern Europe are affecting the level of intrafirm imports from that region. These factors also favor outsourcing over offshoring. In contrast, low organizational costs of hierarchies and large costs of holdup (when there are no alternative investors in Old Europe or no alternative suppliers in Eastern Europe) favor offshoring over outsourcing. Tax holidays granted by host countries in Eastern Europe also mildly affect the organizational choice.
urn:nbn:de:bvb:19-epub-13471-5
Keywords: D23; D51; F11; L14; O11; 330; the empirics of global sourcing; intrafirm trade; contract enforcement; comparative advantage in Eastern Europe; empirical test of the theory of the firm